2016
DOI: 10.1177/0145721715624969
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Health Literacy and Unintentional and Intentional Medication Nonadherence in Medically Underserved Patients With Type 2 Diabetes

Abstract: Structured Abstract Purpose The purpose of this study was to investigate the relationship between health literacy and overall medication nonadherence, unintentional nonadherence, and intentional nonadherence. Limited health literacy may be associated with worse diabetes outcomes, but the literature shows mixed results and mechanisms remain unclear. Medication adherence is associated with diabetes outcomes and may be a mediating factor. Distinguishing between unintentional and intentional nonadherence may eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 41 publications
(90 reference statements)
1
34
0
8
Order By: Relevance
“…This topic has received special attention by the scientific community as a focus for research. Specifically, a systematic review of the literature demonstrated that subjects with lower levels of health literacy are more likely to experience worse health outcomes. Following the lead of medicine, researchers have conceptualized a similar construct for the oral health field.…”
Section: Introductionmentioning
confidence: 99%
“…This topic has received special attention by the scientific community as a focus for research. Specifically, a systematic review of the literature demonstrated that subjects with lower levels of health literacy are more likely to experience worse health outcomes. Following the lead of medicine, researchers have conceptualized a similar construct for the oral health field.…”
Section: Introductionmentioning
confidence: 99%
“…El estudio de la AS y su relación con los resultados en salud, se ha realizado principalmente en individuos con enfermedades crónicas no transmisibles como hipertensión y diabetes, de igual forma se ha examinado su impacto en la adherencia a los medicamentos y su implicación social (11,15,21) . Algunos estudios realizados en Estados Unidos de Norteamérica y Holanda, en pacientes con diabetes tipo 2 encuentran que la baja AS se asocia con la presencia de complicaciones y con el descontrol glucémico (22,23,16) .…”
Section: Discussionunclassified
“…A literacia em saúde, ou as "competências cognitivas e sociais e a capacidade dos indivíduos para ganharem acesso a compreenderem e a usarem informação de formas que promovam e mantenham boa saúde" 31 é um possível mecanismo explicativo da relação entre o nível educacional e as desigualdades em saúde. Revelou estar associada em vários estudos com menores conhecimentos sobre a diabetes, 32 baixa adesão não intencional à terapêutica na diabetes 33 e constituir uma barreira na acessibilidade aos serviços e informação de saúde e aos meios de prevenção. 34 O rendimento também se associou à desigualdade observada mas com menor efeito.…”
Section: Discussionunclassified